Disjunctivism : contemporary readings - Byrne, Alex, 1960-; Logue, Heather, 1979- (MIT readers in contemporary philosophy., 2009)
This reader collects in one volume classic texts that define and react to disjunctivism. These include an excerpt from a book by the late J.M. Hinton.